Research into freight transport queuing at customs control posts - Jarašūniene, Aldona (Transport, 2005)
The changes after Lithuania joined the EU and customs union are analyzed here. For the transport flows forecast and the analysis of traffic at the border theories of multidimensional regression, correlation analysis and wholesale service flows are applied here, the statistical data is processed. According to these mathematical theories and methods a transport flow which will cross the outer border of the EU is forecasted. The method how to predict the amount of transport at a certain border is shown here. The research is performed to find out which custom links have problems. Conclusions and few suggestions how to quicken road traffic flows through Lithuanian customs are also presented in this work.First Published Online: 27 Oct 2010